THE ROLE OF CORPORATE DIRECTOR IN STRATEGIC DECISION-MAKING: A DIALECTICAL APPROACH - NIKI LUKVIARMAN (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2005)
The study conducted by Rindova (1999) has given us a model of the director's contribution to strategic decision-making from the view of cognitive perspective. This model suggests that directors can contribute to strategic decison-making by performing, along with a firm's managers, a set of cognitive tasks: scanning, interpretation and choice. This paper attempts to critically evaluate this model and offers alternative factors and other issues to be considered in relation to director's involvement in strategy processes.